Identifikasi Kualitas Udang Segar Menggunakan Metode Gray Level Co-Occurance Matrix dan Artificial Neural Network : - - Wanda Aprilia Pangemanan; Irma Surya Kumala Idris (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2022)
This study is conducted to know the fresh shrimp quality. In this study, the data collection is through images of shrimp of a variety of sizes and with the number of classes. There are two classes, namely fresh and not fresh. This study is observed independently. The methods used in this study are the Gray Level Co-occurrence Matrix and Artificial Neural Network methods. The performance of using the GLCM and ANN methods in the identification process of fresh shrimp quality indicates a very good performance as proven by the accuracy of 93%, recall of 100%, the precision of 90%, and an F1 score of 95%. Keywords: fresh shrimp quality, GLCM, ANN